The Influence of Loosepart Media in Enhancing Early Childhood Creativity - Muarofakh; Wiwik Lestari; Nuraini; Nasratun Najiha; Suyadi (JOYCED: Journal of Early Childhood Education, 2022)
It is undeniable that the COVID-19 pandemic has had a tremendous impact on society, especially in early childhood. Government policies to study from home increase stress both among parents and students. Teachers must design fun learning for children to attract children's interest in learning from home. This study provides an overview of the influence of loose part materials on children's creativity to provide an overview to educators and parents to utilize loose part materials in the surrounding environment. This research is qualitative descriptive research with the subjects in this study were children aged 4-7 years. Meanwhile, the sources of information or informants can be teachers and parents. Data collection in the field using observation, interviews, and documentation. The analysis technique used is a data reduction technique to focus attention and select the data needed in research, presentation of data, and withdrawal of conclusions. The results show that loose part media has a tremendous influence on the development of children's creativity. Children can explore and experiment with loose parts to form works according to their imagination.